ПАРАБОЛО-ГИПЕРБОЛИК ТИПДАГИ МОДЕЛ ТЕНГЛАМА УЧУН НОЛОКАЛ МАСАЛАЛАР (Scientific journal of the Fergana State University, 2023)
In the paper a non-local problem with Bitsadze-Samarskii type condition has benn formulated and investigated for a model parabolic-hyperbolic type equation